Experience of implementing a value-based approach in oncodermatology - Yu. A. Zuenkova; D. I. Kicha; L. N. Izyurov (Фармакоэкономика)
Objective: implementation of value-based approach and development of adherence to treatment in patients with non-melanoma cancer.Material and methods. The observational, single-arm, prospective, long-term single-center study of the quality of life and patients’ experience was performed. It included 42 patients aged from 42 to 82 years. Validated questionnaires were used: Patient-Reported Outcome Measures (PROMs) (as a decision support tool), Patient-Reported Experience Measures (PREMs) (3 months after treatment to assess the patient's experience).Results. Mean concern about appearance was 43.5 points (Rasch psychometric model). Younger patients (r=–0.398, p=0.009) and female patients (r=–0.475, p=0.001) were more concerned about appearance. In 10 cases (24%), the involvement was estimated as 4 points, in 18 cases (43%), it was 3 points, in 14 cases (33%), it was 2 points. Older patients were less involved in the choice of treatment method (r=–0633, p<0.001). The level of satisfaction with communications was more than 50 points. The use of a patient-oriented algorithm of communication has a positive effect on a patient's experience.Conclusion. The heads of oncological care are recommended to evaluate the patient's experience on a regular basis, create conditions for patients to choose treatment methods according to their individual needs, analyze the outcomes obtained by the introduction of validated questionnaires on the appropriate nosological profile and take these results into account in treatment. Further studies of the degree of influence of different factors on a patient’s choice of treatment method are needed, as well as conducting studies among other groups of patients with non-melanoma skin cancer (located in other parts of the body, larger than 2 cm).